Colonic endometriosis: Diagnostic and therapeutic considerations - Piñeyro, Alberto; Carriquiry, Luis; Scigliano, Horacio; Ardao, Gonzalo (Cirugía del Uruguay, 1991)
Two cases of endometriosis of the colon were presented. Their etiological, pathogenic, pathological and clinical aspects, as a/so the most important laboratory studies, were discussed. Regarding treatment it was pointed out that, in view of these symtomatic endometriosis of the colon, a resection of the intestine needs to be performed